Secondary Students' Preference for (Non)Yorùbá Films: A Cognitive film Perspective - Ifeoluwa Akinsola (International Journal of Studies in Psychology)
This study evaluated students’ preferences for Yoruba and non-Yoruba films. It also explored factors that affect students’ film preferences in relation to the teaching and learning of Yorùbá language and culture from the cognitivist's perspective. It adopted mixed methods research design of the sequential explanatory. Three Hundred (300) Senior Secondary Two (SS II) students were randomly selected from 10 public secondary schools in Ibadan North Local Government Area, in Nigeria. The self-designed Students’ Questionnaire on Film Preferences (r=.93) was used for data collection. Also, seven (7) SS II students were selected for a Focused Group Discussion in each of the selected schools. Quantitative data were analysed using the t-test analysis (p<0.05), while the qualitative one was thematically analysed. Findings revealed that the secondary students’ preference for Yorùbá and non-Yoruba films was significantly differed (t(299) = -6.53; p<0.05), in favour of the latter (mean =38.05). The results reported that home, socio-cultural and recreational factors could be responsible for students’ film preferences. Based on the principles of Cognitive Film Theory, the study argues that students' film preference has attitudinal and pedagogical implications. Therefore, Yorùbá language teachers should regularly sensitise and encourage students to watch Yorùbá Films that can enhance their cognition of the Yorùbá cultural practices.